1994
DOI: 10.1007/bf02631276
|View full text |Cite
|
Sign up to set email alerts
|

Roles for insulin and ecdysteroids in differentiation of an insect cell line of epidermal origin

Abstract: During postembryonic development of insects, molting cycles affect epidermal cells with alternate periods of proliferation and differentiation. Cells of the cell line established from imaginal discs of the Indian meal moth (IAL-PID2) differentiate under the action of the molting hormone, 20-hydroxyecdysone, in a manner that is meaningful in terms of the development of the tissue from which they were derived. In particular, the hormone caused an accumulation of the cells in the G2 phase of their cycle and induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 18 publications
2
16
0
Order By: Relevance
“…In accord with published observations, we found that treatment of S2 cells with ecdysone caused a rapid and severe G 2 /M phase cell cycle block (Fig. 7C) (4,8,11,19,53). Thus, the SIN3/RPD3 complex, SMRTER, and EcR are required at similar points in the cell cycle.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In accord with published observations, we found that treatment of S2 cells with ecdysone caused a rapid and severe G 2 /M phase cell cycle block (Fig. 7C) (4,8,11,19,53). Thus, the SIN3/RPD3 complex, SMRTER, and EcR are required at similar points in the cell cycle.…”
Section: Resultssupporting
confidence: 92%
“…These observations highlight the importance of the balance of histone acetylationdeacetylation during the cell cycle. The SIN3/RPD3 deacetylase complex may participate in regulation of G 2 cell cycle progression, as ecdysone treatment of Drosophila tissue culture cells causes arrest in the G 2 phase of the cell cycle (4,9,11,19).…”
mentioning
confidence: 99%
“…A comparison of the sequences of the synthetic peptides is presented in Figure 8. Unlike MDF1 and 2, MDF3 and 4 were not homologous to other peptides or proteins in the Swissprot database (BLAST) (Altschul et al, 1997), or to known insect growth factors or cytokines (Ebberink et al, 1989;Hatt et al, 1994;Ferkovich et al, 1995;Homma et al, 1996;Strand et al, 2000). All of the natural and synthetic MDF peptides induced dosedependent differentiation of H. virescens midgut stem cells to mature goblet and columnar cells in vitro, and induced similar effects when introduced alone at the same concentrations in this work.…”
Section: Discussionsupporting
confidence: 60%
“…The growth-promoting activity of insulin and insulin-like growth factors has been amply documented in both vertebrate cells and organ cultures. In insect cell cultures, exogenous insulin and insulin-like growth factors provoke physiological effects (Seecof and Dewhurst, 1974;Davis and Shearn, 1977;Martin and Shearn, 1980;Mosna, 1981;Wyss, 1982;Cullen and Milner, 1991;Hatt et al, 1994Hatt et al, , 1997 and mammalian insulin is presently a routine additive to Drosophila culture media (Wyss, 1988;Echalier, 1997). Nijhout and Grunert (2002) reported that bombyxin-II stimulates cell division and growth of wing imaginal disks of Precis coenia.…”
Section: Discussionmentioning
confidence: 99%